2012
DOI: 10.1158/0008-5472.can-12-0006
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/Snail Signaling Regulates CytochromecOxidase and Glucose Metabolism

Abstract: Wnt signaling plays a critical role in embryonic development, and its deregulation is closely linked to the occurrence of a number of malignant tumors, including breast and colon cancer. The pathway also induces Snail-dependent epithelial-to-mesenchymal transition (EMT), which is responsible for tumor invasion and metastasis. In this study, we show that Wnt suppresses mitochondrial respiration and cytochrome C oxidase (COX)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 50 publications
2
170
0
Order By: Relevance
“…Increasing the expression of COX-2 and its product PGE2 activates the b-catenin/TCF4 pathway and has been implicated in cancer tumorigenesis and EMT. 54,55 Our findings confirmed that the expression of PLC-g2 and TCF4 was increased after NPC cells were co-cultured with T-MDSCs but decreased in siCOX-2-treated cancer cells. Therefore, T-MDSCs induce EMT via the showing that tumoractivated MDSCs induce EMT via multiple pathways, including TGFb, HGH, and TGH, in melanoma.…”
Section: Discussionsupporting
confidence: 75%
“…Increasing the expression of COX-2 and its product PGE2 activates the b-catenin/TCF4 pathway and has been implicated in cancer tumorigenesis and EMT. 54,55 Our findings confirmed that the expression of PLC-g2 and TCF4 was increased after NPC cells were co-cultured with T-MDSCs but decreased in siCOX-2-treated cancer cells. Therefore, T-MDSCs induce EMT via the showing that tumoractivated MDSCs induce EMT via multiple pathways, including TGFb, HGH, and TGH, in melanoma.…”
Section: Discussionsupporting
confidence: 75%
“…In this study it was reported that the activation of Wnt repressed mitochondrial cytochrome oxidase (COX) expression con-comitantly with the stimulation of lactate production. Surprisingly, PC expression was enhanced, suggesting a possible activation of the anaplerotic pathways [81]. These results seem contradictory as they imply the induction of the aerobic glycolysis, while anaplerosis is indicative of a high Krebs cycle activity.…”
Section: Pyruvate Carboxylasementioning
confidence: 88%
“…However, more recently, direct associations have been demonstrated for control of cancer cell metabolism by the canonical WNT pathway. In breast cancer, for example, WNT/␤-catenin signaling increases aerobic glycolysis through suppression of mitochondrial respiration by reducing the transcription of the gene for cytochrome c oxidase, which is an integral enzyme of the ETC and thus essential for OXPHOS (12). Furthermore, in triple-negative breast cancer cells, WNT5B was recently shown to be able to control the expression of the OX-PHOS-related genes for cytochrome c 1 and the ATP synthase ␥ subunit through the canonical WNT pathway (15).…”
Section: Canonical Wnt Signaling and Cancer Cell Metabolismmentioning
confidence: 99%
“…Recently, evidence has emerged that highlights a role for WNT-mediated regulation of cellular metabolism as well, including the reprogramming of tumor cell bioenergetics (12)(13)(14)(15). This review explores the evidence that components of the WNT signaling pathways regulate cellular metabolism with a specific focus on cancer cells.…”
mentioning
confidence: 99%